2021
DOI: 10.5858/arpa.2020-0497-oa
|View full text |Cite
|
Sign up to set email alerts
|

Mucocele-like Lesion of the Breast Diagnosed on Core Biopsy

Abstract: Context.— Mucocele-like lesion of the breast (MLL) is an uncommon entity, and recent studies show low rates of upgrade from core needle biopsy (CNB) to excision. Objective.— To evaluate features associated with upgrade of MLLs diagnosed on CNB. Design.— Seventy-eight MLLs diagnosed on CNB from 1998–2019 and subsequent excisions were reviewed. Histologic param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…However, calcifications may help determine the risk for malignancy. Towne et al reported that all of their MLL cases contained widespread coarse calcifications that were upgraded following CNB, suggesting an association between coarse calcifications and higher upgrade rates [9]. Consistent with previous reports, our patient presented with coarse calcifications on her initial mammogram, and a follow-up ultrasound was recommended.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, calcifications may help determine the risk for malignancy. Towne et al reported that all of their MLL cases contained widespread coarse calcifications that were upgraded following CNB, suggesting an association between coarse calcifications and higher upgrade rates [9]. Consistent with previous reports, our patient presented with coarse calcifications on her initial mammogram, and a follow-up ultrasound was recommended.…”
Section: Discussionsupporting
confidence: 89%
“…However, more recent studies are proposing selective excision based on the histology of the lesion. One study found that MLLs with atypia were upgraded to DCIS twice as often as samples without atypia, occurring in approximately half of the biopsies [9]. Another study found that 28 out of the 53 MLL lesions analyzed were malignant, with 14 being in situ and the other 14 being invasive [13].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound can demonstrate hypoechoic oval masses, complex cysts with or without associated calcifications, clustered cysts, cysts with thick septations, complex masses (solid-cystic), or tubular masses with low-level internal echoes [10] . There are few reports of mucocele-like cases with magnetic resonance imaging (MRI), being reported as irregular masses with heterogeneous enhancement or nonmass enhancements [ [7] , [11] , [12] ]. There are no specific imaging criteria to predict atypia or malignancy [10] .…”
Section: Discussionmentioning
confidence: 99%
“…About 11%-57% of the MLLs are associated with ADH [ [3] , [7] ] and 2%-30% are associated with DCIS [3] . The upgrade rate to DCIS for MLL with atypia is 8%-75% and for MLL without atypia is 2.8%-13% ( Table 1 ) [ [5] , [8] , [9] , [11] , [15] , [16] , [17] ]. The atypical hyperplasia can be found outside the area of MLL in 26% of the ADH and 88% of the ALH [4] , reflecting the heterogeneous background of these lesions and reaffirming the importance of a good sampling, not only the visible target.…”
Section: Management After a Diagnosis Of Mll On A Percutaneous Biopsymentioning
confidence: 99%
“…If the calcifications extend over a significant area on imaging, MDT discussion is needed to determine if excision is needed [78,79]. MLLs associated with atypical epithelial hyperplasia are frequently subjected to excision due to the risk of lesional upgrade reported in up to 15-20% for patients with MLL-associated atypia [76,80,81]. MLLs with DCIS or invasive carcinoma are managed accordingly.…”
Section: How Should Microinvasion On Core Biopsy Be Managed?mentioning
confidence: 99%